Burden and Life Satisfaction among Caregivers of Hemodialysis Patients Residing in Kathmandu - Maharjan, Mankeshari; Silwal, Ajita; Adhikari, Bebita; Thapa, Bandana; Bhandari, Bhagawati; Shrestha, Sangita (Journal of Karnali Academy of Health Sciences, 2021)
Introduction: The patients undergoing hemodialysis need long-term care. Caregivers of hemodialysis patients can suffer from physical and psychological stress that can affect the level of burden and life satisfaction among them. The objective of the study was to assess burden and the life satisfaction among caregivers of hemodialysis patients. Methods: A cross-sectional study was conducted among 167 caregivers of hemodialysis patients in Bir Hospital and National Kidney Center from December 2019 to March 2020 by using a proportionate sampling technique. Zarit Burden Interview-22 (ZBI) was used to assess the level of caregiver burden and the Life Satisfaction Questionnaire (LiSat-11) was used to assess life satisfaction among caregivers. Frequency, percentage, mean and standard deviation were used for descriptive analysis. Chi-square analysis was used to find out the association between the level of caregiver burden and socio-demographic variables. Spearman correlation was used to analyze the correlation between burden and life satisfaction among caregivers of hemodialysis patients. Results: Out of 167 participants, 89 (53.3%) had a mild to moderate level of burden. Only 6 (3.6%) of them had a severe burden. The mean satisfaction score was 36.89±7.03. Marital status, the number of children, and annual income had a statistically significant association with the level of burden. A negative correlation was found between burden and life satisfaction which was statistically significant (r=-0.441; p value=<0.001). Conclusion: The majority of caregivers were satisfied in terms of life as a whole, leisure situation, contacts, sexual life, activities, family life, partner relationships, physical and psychological health. However, the level of burden was found to be high among caregivers of hemodialysis patients. Necessary support interventions should be carried out to improve their caring roles and coping strategies.